Cyclic Fatigue Resistance of One G, WaveOne Gold Glider, T-Endo MUST and VDW.ROTATE Glide Path Instruments at Root Canal Temperature - Seda Falakaloğlu; Ahmet Uygun (Mashhad University of Medical Sciences, 2021)
Introduction: This study was conducted to compare the cyclic fatigue (CF) resistance of One G, WaveOne Gold Glider, T-Endo MUST tg, One G and VDW.ROTATE nickel-titanium (NiTi) glide path (GP) instruments in a simulated canal of 900 and a 3-mm radius canals at root canal temperature. Methods: Sixty NiTi files were used for the fatigue testing in stainless steel canals compatible with instrument sizes until fracture occurred (n=15): One G (#14/.03), WaveOne Gold Glider (#15/.02), T-Endo MUST tg (#13/.04), VDW.ROTATE (#15/.04), The number of cycles to fracture (NCF) was calculated for each instrument, and the lengths of the detached fragments (LDF) were measured. Data were statistically analyzed using the Kruskal-Wallis analysis and Mann-Whitney U tests at the %95 confidence level. Results: There were significant differences in the CF resistance among the groups (P < 0.05), the highest to lowest NCF values of the files as follows: T-Endo MUST tg, WaveOne Gold Glider, VDW.ROTATE, and One G. There was no significant difference within LDF among the groups P> 0.05). Conclusion: The T-Endo MUST tg files had the highest and the One G files had the lowest CF resistance in a simulated canal of 900 and 3-mm radius canals at root canal temperature